Effectiveness of Physical Activity: Silent Walking on Cognitive Impairment in Young Adults - Surani, Vincencius; Pranata, Lilik; Hardika, Bangun Dwi; Daeli, Novita Elisabeth; Suryani, Ketut; Rini, Maria Tarisia; Aprezia, Tezi Kharina (Journal of Health Science and Medical Therapy, 2025)
Physical activity is an activity that we often do, especially walking, so far we have considered walking to be tiring, but it has great benefits for our body physiology both mentally, cognitively and physically, managing emotional functions related to cognitive function. Cognitive is an important part of humans in thinking and reasoning. Especially with the many activities of the younger generation today but who are less sensitive to their health, so that they are at risk of cognitive disorders. One can be done by walking. The purpose of the study was to determine the Effectiveness of Physical Activity: Walking on Cognitive Disorders in young adults. The research method used a pre-experimental pretest and posttest design with control, with a total of 44 samples, consisting of 22 interventions and 22 controls, walking activities were carried out for three consecutive days, with a duration of 60 minutes, at 16.00-17.00 WIB, on December 16-18, 2024. The sample criteria were first-year nursing students who carried out walking activities continuously for three days. The results of the study showed that the significance value of cognitive impairment obtained was (Z = -2.646, p = 0.008). This means that there is a significant difference in the level of cognitive impairment between before and after the intervention of physical activity. The significance value of cognitive impairment obtained was (Z = 0.000, p = 1.000). This means that there is no difference in the level of cognitive impairment in the control group. The significance value of cognitive impairment obtained was (Z = -,935, p = 0.350). This means that there is no significant difference in the level of cognitive impairment between the intervention group and the control group after the intervention of physical activity. These results explain that there is no significant difference between intervention and control. Suggestions are that there needs to be continuous and periodic activities so that the results can be maximized, because cognitive cannot change simultaneously, so it must be accompanied by routine activities, not just incidental activities, to get good results.